Peran Dan Manfaat Mobile Banking Dalam Mengurangi Antrian Nasabah: Tinjauan Aspek Manajemen Operasional Bank XYZ - Gian Rijaldi; Novi Sari Dewi; Fathul Arifin; Tri Ngudi Wiyatno; Sunita Dasman (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the role and benefits of mobile banking in reducing customer queues from an operational management perspective at Bank XYZ. The research employed a qualitative approach using interviews and descriptive techniques. The results indicated that six frontliners agreed mobile banking effectively reduces queue volume. This is supported by the increasing number of users utilizing the application for various transactions such as fund transfers, cash withdrawals, and bill payments. Additional benefits include improved employee efficiency and reduced operational costs. For customers, mobile banking offers convenience by allowing transactions anytime and anywhere without visiting a bank branch.